South Africa: Regionality and Defense - Dall'Agnol, Gustavo; de Conti Pagliari, Graciela; Jolkesky, George (Revista de Geopolítica, 2025)
This paper seeks to elucidate why certain middle powers with regional influence do not pursue regional hegemony, contrary to theoretical expectations. Offensive Realism and Historical Sociology posit that states are compelled to maximize their power, particularly in terms of material capabilities. This study examines the case of South Africa, a notable example of a state reducing its defense budget and material capabilities within an unbalanced multipolar order. From a realist perspective, a low threat level is a key variable explaining a state's decision not to enhance its capabilities. However, this factor alone is insufficient to fully account for South Africa's behavior. A domestic perspective, focusing on elite decision-making processes, is also necessary.